PENGARUH EDUKASI FIRST AID TRAINING TERHADAP TINGKAT PENGETAHUAN GURU SD - Pujiastutik, Yanuar Eka (STIKES NGUDIA HUSADA MADURA, 2024)
The community service activities currently being carried out are in the form of a safety promotion programproviding first aid training for elementary school teachers in Timor Leste. This activity is carried out through onlineactivities using zoom in the form of educational first aid training held in May 2024. The targets of this communityservice activity are elementary school teachers in Timor Leste, in this case teachers of grades 1 to 6.Implementation of community service activities begins with a pre-test use a questionnaire to determine the levelof knowledge about first aid when an accident occurs. After the pre-test results are obtained, education is carriedout. Evaluation of the implementation of community service activities shows that there has been a 26% increasein knowledge regarding first aid, handling shock, choking on food, exposure to chemicals, insect stings, poisoning,burns, cuts, bleeding, broken bones, sprains, respiratory arrest and cardiac arrest. It is hoped that this communityservice activity will take place in stages with other types of basic assistance that can be provided if an accidentoccurs.